A review on antibacterial silk fibroin-based biomaterials: current state and prospects. (March 2022) - Ghalei, S.; Handa, H.
Abstract: Bacterial contamination of biomaterials is a common problem and a serious threat to human health worldwide. Therefore, the development of multifunctional biomaterials that possess antibacterial properties and can resist infection is a continual goal for biomedical applications. Silk fibroin (SF), approved by the United States Food and Drug Administration as a biomaterial, is one of the most widely studied natural polymers for biomedical applications owing to its unique mechanical properties, biocompatibility, tunable biodegradation, and versatile material formats. In the last decade, many methods have been used for the development of antibacterial SF-based biomaterials (SFBs) such as physical loading or chemical functionalization of SFBs with different antibacterial agents and bioinspired surface modifications. In this review, we first describe the current understanding of the composition and structure-property relationship of SF as a leading-edge biomaterial. Then we demonstrate the different antibacterial agents and methods implemented for the development of bactericidal SFBs, their mechanisms of action, and different applications. We briefly address their fabrication methods, advantages, and limitations, and finally discuss the emerging technologies and future trends in this research area. Graphical abstract: Image 1 Highlights: An overview of silk fibroin structure-property relationship as a leading-edge biomaterial. A comprehensive summary of different approaches for development of antibacterial silk fibroin-based biomaterials. Illustrating the currently used fabrication methods for these biomaterials and their biomedical applications. Describing the promises and pitfalls of each antibacterial approach and identifying the emerging trend for future research.